PROSPECT OF USING PROPOLIS IN CONSERVATIVE DENTISTRY AND ENDODONTIC TREATMENT (BASIC RESEARCH VS CLINICAL APPLICATION): PROSPEK PENGGUNAAN PROPOLIS DALAM BIDANG OPERATIVE DENTISTRY DAN PERAWATAN ENDODONTI (PENELITIAN DASAR VS APLIKASI KLINIS - Ardo Sabir (TALENTA, 2014)
Propolis is a resinous hive product, collected by bees from tree buds and mixed with secreted bee wax in order to avoidbacterial contamination in the hive, and also to seal it. It is acknowledged that propolis has antimicrobial activity as wellas anti-inflammatory, antioxidant, antitumor, immuno-regulatory, and regenerative tissue properties. Chemically, propolisis exceedingly complex and contains a rich variety of potent terpene, benzoic, caffeic, cinnamic, aromatic aldehyde,phenolic acid, and also high in flavonoid. Recently, propolis has been the subject of several studies, both in vitro and invivo or even at animal or human with the aim to elucidate its biological and pharmacological properties. The use ofpropolis in dentistry has been done in few years ago for various purposes such as in treatment of periodontitis and dentalcaries, to accelerate the healing of post-extraction wounds, to treat aphthous stomatitis, as a storage media following teethavulsion. The result of basic research of propolis apparently was useful to support its clinical application in dentistry.However, standardization the composition of propolis due to its chemical diversity is still a problem. Therefore thepurposes of this review article were (1) to explain the prospect of propolis in conservative dentistry and endodontictreatment, and (2) to stimulate the interest of clinicians to make further research about this natural compound in dentistry.In conclusion, propolis is a natural medication with a promising future but further studies should be conducted toinvestigate its merit and demerits in clinical dentistry